Motivasi Primipara dalam Pemberian ASI Eksklusif - Tetik Nurhayati (FORIKES, 2021)
Currently there are still many mothers who have not exclusive breastfeeding their babies from 0 to 6 months of age, this is due to several problems. Some of the obstacles in exclusive breastfeeding are that mothers lack confidence to be able to breastfeed properly so that they can meet all the nutritional needs of their babies and lack of motivation, especially for mothers who have had children for the first time. Descriptive research design. The number of respondents was 15 people who were selected by consecutive sampling. The research location was the Integrated Service Post Jimbe, Plalangan, Singosaren, Setono, Mrican, and Krajan 2. The instrument used was a motivational questionnaire to provide exclusive breastfeeding made by the researcher. Based on the research results, all 15 respondents have moderate motivation. The factor that most influences primipara motivation in exclusive breastfeeding is age.The results of this study are recommendations for future researchers to conduct research on counseling for mothers in providing exclusive breastfeedingKeywords: exclusive breastfeeding; motivation; primiparaABSTRAKSaat ini masih banyak ibu-ibu yang belum memberikan ASI eksklusif pada bayinya dari usia 0 hingga 6 bulan, hal ini disebabkan beberapa permasalahan. Beberapa kendala dalam pemberian ASI Eksklusif adalah kurangnya rasa percaya diri ibu untuk dapat menyusui dengan baik sehingga dapat memenuhi semua kebutuhan gizi bayinya serta kurangnya motivasi terutama bagi ibu yang baru pertama kali memiliki anak. Desain penelitian deskriptif. Jumlah responden sebanyak 15 orang yang dipilih secara consecutive sampling. Lokasi penelitian adalah Pos Pelayanan Terpadu Jimbe, Plalangan, Singosaren, Setono, Mrican, dan Krajan 2. Instrumen yang digunakan adalah angket motivasi dalam memberikan ASI Eksklusif yang dibuat oleh peneliti. Berdasarkan hasil penelitian, sebanyak 15 responden memiliki motivasi sedang. Faktor yang paling mempengaruhi motivasi primipara dalam pemberian ASI Eksklusif adalah usia. Hasil penelitian ini menjadi rekomendasi bagi peneliti selanjutnya untuk melakukan penelitian tentang penyuluhan bagi ibu dalam memberikan ASI eksklusifKata kunci: ASI eksklusif; motivasi; primipara